Increasing metro line capacity by optimisation of track circuit in a speed code Automatic Train Protection system. (January 2016) - Mera, JM; Carabaño, E; Soler, M; Castellote, E
When analyzing a railway operation, multiple issues must be taken into account to obtain the best results in terms of safety, efficiency and flexibility. In this project, carried out in collaboration between CITEF and a European metro line, a tool has been developed and implemented. Based on the line data provided by the metro line, the signalling system (distance to go/speed signalling), the main characteristics of the rolling stock, etc., information can be obtained for modelling/modifying the line, changing or removing/inserting track circuits or even changing the maximum running speeds on those track circuits. Travel times, line frequencies, bottlenecks, and degraded conditions are also analyzed from the simulations, so that finally the best headway to be implemented on the line can be proposed for the user, who is able to know how to improve the main line features like capacity and frequency of trains. Integrating distance to go and speed signalling into the set of parameters, is another capability proposed. Fundamental information on the signalling system capacity can be obtained simply by running the algorithms designed for this task along with the changes in order to carry it out.